1996
DOI: 10.1111/j.1749-6632.1996.tb33502.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection by Ischemic and Nonischemic Myocardial Stress and Ischemia in Remote Organs Implications for the Concept of Ischemic Preconditioninga

Abstract: Ischemic preconditioning studies employ one or more brief total coronary artery occlusions separated by complete reperfusion to limit infarct size during a subsequent prolonged coronary artery occlusion. We now present evidence that in anesthetized pigs a partial coronary artery occlusion without intervening reperfusion between the partial and prolonged total occlusions can also precondition the myocardium provided that the reduction in coronary blood flow is sufficiently severe. Thus infarct size was reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…This so-called ischemic preconditioning has been attributed to local protective mechanisms, including induction of heatshock proteins 29 and adenosine formation. 30 However, brief ischemia in remote organs 31,32 or endotoxin pretreatment 4 -6 has been shown to confer similar protection, suggesting involvement of other than local mechanisms. Indeed, the observed I/R-induced SAP and AGP increase and elevated hepatic acute phase protein mRNA content show that renal I/R induces an APR.…”
Section: Discussionmentioning
confidence: 99%
“…This so-called ischemic preconditioning has been attributed to local protective mechanisms, including induction of heatshock proteins 29 and adenosine formation. 30 However, brief ischemia in remote organs 31,32 or endotoxin pretreatment 4 -6 has been shown to confer similar protection, suggesting involvement of other than local mechanisms. Indeed, the observed I/R-induced SAP and AGP increase and elevated hepatic acute phase protein mRNA content show that renal I/R induces an APR.…”
Section: Discussionmentioning
confidence: 99%
“…In the experimental setting, a further approach of myocardial protection has been observed after short ischemic episodes of peripheral tissues, a process termed remote ischemic preconditioning (2,14). Cytoprotection in the heart has been demonstrated after ischemia in a variety of peripheral tissues, such as the mesenterium, kidney, and skeletal muscle (12,32). Of these, skeletal muscles have attracted considerable scientific interest because they are easily accessible and can be manipulated without major risk in the clinical setting, should this method prove of therapeutic value.…”
mentioning
confidence: 99%
“…Verdouw et al were the first to report a real remote IP of the heart by mesenteric artery occlusion in a rat model. 42 The protective influence of limb ischemia on myocardial infarction was reported by Birnbaum et al 43 and Oxman et al 44 A study from our laboratory on remote IP of flaps showed, in a rat adipocutaneous flap model, that acute IP and enhancement of flap survival can be achieved not only by preclamping of the flap pedicle, but also by induction of an ischemia/reperfusion event in a body area distant from the flap prior to elevation. 45 An invasive procedure clamping the femoral artery was as effective to precondition the flap as a noninvasive tourniquet application to a rat hindlimb followed by 30 min of limb reperfusion (Figs.…”
Section: Remote Ischemic Preconditioningmentioning
confidence: 87%